Overdense plasma generation in a compact ion source. (6th April 2017) - Castro, G; Mascali, D; Gammino, S; Torrisi, G; Romano, F P; Celona, L; Altana, C; Caliri, C; Gambino, N; Lanaia, D; Miracoli, R; Neri, L; et al.
Abstract: Electron cyclotron resonance ion sources (ECRIS) are widely used plasma based machines for the production of intense ion beams in science and industry. The performance of modern devices is limited by the presence of the density cut-off, above which electromagnetic (EM) waves sustaining the plasma are reflected. We hereby discuss the systematic data analysis of electrostatic wave generation in an ECR prototype operating at 3.75 GHz–0.1 THz. In particular, electron Bernstein waves (EBW) have been excited. EBW have already been generated in large-scale plasma devices for thermonuclear fusion purposes. In ion sources where L c  ∼  λ RF ( L c being the plasma chamber size and λ RF the pumping wave wavelength) the EM field assumes a modal behaviour; thus both plasma and EM field self-organize so that no optical-like wave launching is possible (i.e. the cavity effect dominates on the optical path). The collected data, however, supported by 3D full-wave simulations, actually demonstrate that a Budden-type X-B conversion scenario can be established above some critical RF power thresholds, operating in an off-ECR regime. The generation and absorption of the EBW has been demonstrated by the presence of three peculiar signatures: along with the establishment of an overdense plasma, generation of supra-thermal electrons and modification (non-linear broadening) of the EM spectrum measured within the plasma have been observed. At the threshold establishing such a heating regime, the collected data provide evidence for a fast rotation of the electron fluid.